Father's Attachment and Its Implications for Children's Self-Confidence in Kindergarten - Silvie Mil; Devvi Natasha (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2025)
In the Jatimurni sub-district of Bekasi City, this study is to examine the relationship between father attachment and self-confidence in children aged 5 to 6. This study's foundation is the observation that, in Indonesia, fathers are not actively involved in their children's upbringing, which has negative effects on their children's social and emotional development, especially their self-confidence. Involving 104 dads and children between the ages of 5 and 6, the study method used a correlational quantitative approach with a purposive sample strategy. A validated and reliable questionnaire serves as the research tool. A basic linear regression and Spearman's rho correlation test are used in data analysis. A correlation coefficient of 0.752 and a R Squared value of 0.566 indicate that there is a strong relationship between father attachment and self-confidence in young children. Except for the father's connection, which is affected by variables not included in this research. The significance of the father's involvement in fostering self-confidence in children from a young age is highlighted by these results, which support Bowlby's attachment theory. Family education programs and social support should be more prominent in raising dads' consciousness of their roles as active participants in their children's upbringing, according to the research's practical implications. Additional research into the elements that influence children's self-confidence is needed, according to this study.